تعايم اللغة العربية لأغراض خاصة: تجارب وتقويم = Ta'lim al-lughah al-arabiyah li aghradh khassah: tajarib wa taqwim - Chik, Abdul Rahman; Sa'ed, Jam'an; Abdul Wahid, Ali; Abu Amshah, Khalid Husein; Barakat, Al-Sadiq Adam; Yang, Yah Liyang (King Abdullah Bin Abdul Aziz International Centre for the Arabic Language, 2018)
A comprehensive collection of studies conducted by seven experts of Teaching Arabic for Specific Purposes (TASP) from different parts of the world including China, America, Middle East, Turkey and Malaysia.Published by King Abdullah bin AbdulAziz Centre for the Arabic Language, Riyadh.